Comparison of the Definition of remembrance based on verse 152 of surah Al-Baqarah through Tafsir Jalallain and Tafsir Ibn Kathir - Pakhrurrozi Pakhrurrozi; Muhammad Hafizi; Ali Akbar Bin Usman (Journal of Multidisciplinary Sustainability Asean, 2024)
Background.  This study discusses the comparison of the meaning of remembrance based on verse 152 of surah Al-Baqarah through the perspective of two classic tafsir books, namely Tafsir Jalalain and Tafsir Ibn Kathir. This verse emphasizes the importance of remembering Allah as a form of gratitude and obedience. By examining these two commentaries, this research aims to explore the mufassirs' understanding of the concept of remembrance and how it is applied in everyday life. Purpose.. This study aims to analyze and compare the interpretations of dhikr (remembrance of Allah) in verse 152 of Surah Al-Baqarah as presented in Tafsir Jalalain and Tafsir Ibn Kathir. By examining these perspectives, it seeks to reveal their similarities and differences, highlighting the significance of dhikr in the spiritual and daily lives of Muslims. Method.  Examining dhikr according to Tafsir Jalalain, focusing on the form of worship that includes the tongue, heart, and actions, as well as its reward from Allah. Examining dhikr in Tafsir Ibn Kathir as a broad form of worship that invites Allah's protection, as well as the importance of gratitude. Comparing the two commentaries to understand the similarities and differences related to dhikr and gratitude. Results. Tafsir Jalalain and Ibn Kathir agree that dhikr is a comprehensive act of worship (verbal, heart, and deeds), which is rewarded with Allah's mercy. Zikr also includes gratitude as a form of obedience to His favors. Conclusion. The comparison of dhikr interpretations in Tafsir Jalalain and Tafsir Ibn Kathir reveals both similarities and differences. Tafsir Jalalain offers a clear explanation, focusing on dhikr as gratitude and obedience. In contrast, Tafsir Ibn Kathir provides a detailed context through hadith and scholarly views. Both agree on dhikr's crucial role in deepening spiritual connections with Allah and achieving peace and happiness in this life and the hereafter.